2007
DOI: 10.1016/j.jvs.2007.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of the venous outflow in chronic venous disease: Long-term stent-related outcome, clinical, and hemodynamic result

Abstract: Venous stenting can be performed with low morbidity and mortality, long-term high patency rate, and a low rate of in-stent restenosis. It resulted in major symptom relief in patients with chronic venous disease, which was not consistently reflected in any substantial hemodynamic improvement by conventional measurements. The beneficial clinical outcome occurred regardless of presence of remaining reflux, adjunct saphenous procedures, or etiology of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
489
5
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 612 publications
(532 citation statements)
references
References 39 publications
16
489
5
22
Order By: Relevance
“…In a series by Hartung et al, all but 2 of 47 (96 %) ulcers healed after venous stenting [53]. Neglén et al reported a longterm ulcer healing rate of 55 % [49]. These clinical results were proven by several recent studies, which reported significant decrease in the VCSS after stenting of iliocaval obstructions [54] or reduced swelling and pain levels after endovenous treatment [47,55].…”
Section: Effectivenessmentioning
confidence: 93%
See 4 more Smart Citations
“…In a series by Hartung et al, all but 2 of 47 (96 %) ulcers healed after venous stenting [53]. Neglén et al reported a longterm ulcer healing rate of 55 % [49]. These clinical results were proven by several recent studies, which reported significant decrease in the VCSS after stenting of iliocaval obstructions [54] or reduced swelling and pain levels after endovenous treatment [47,55].…”
Section: Effectivenessmentioning
confidence: 93%
“…Two major series from different groups on stenting in postthrombotic iliac vein obstruction report primary, assisted primary and secondary patency rates of 57, 80, and 86 % at 6 years [49] and 83, 89, and 93 % at 10 years, respectively [50]. A detailed analysis of the outcome of stenting in postthrombotic iliocaval obstruction can be found in a recently published review [51].…”
Section: Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations